ЭКОЛОГИЧЕСКИЕ АСПЕКТЫ ДОБЫЧИ МИНЕРАЛЬНОГО СЫРЬЯ - Лифановская С.Ю. (My University, 2010)
Обсуждаются экологические проблемы добычи полезных ископаемых. Характеризуется влияние горнорудной промышленности на почву, атмосферный воздух, водные объекты. Предлагается ряд проектов для решения этих проблем.Ecological problems of mining operations are considered in the article. The description of the ore mining influence on soil, atmospheric air and bodies of water are given characteristics. The set of proposals are given for solving these problems.
Keywords: 504.062.2